1992
DOI: 10.1002/pen.760321308
|View full text |Cite
|
Sign up to set email alerts
|

Blends of polycarbonate with poly(methyl methacrylate): Miscibility, phase continuity, and interfacial adhesion

Abstract: Dynamic mechanical thermal analysis (DMTA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM) concurrently show that polycarbonate (PC)/poly(methyl methacrylate) (PMMA) blends have a two-phase structure. The differences between the Tgs of parent polymers and the Tgs of conjugate phases, determined by both DMTA and DSC, indicate a limited miscibility of components and allow the approximate composition of conjugate phases to be calculated. The Flory-Huggins interaction parameter cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Except for the elongation, the superiority of the SBR-2-containing blends is clear over the SBR-1 counterparts. It is noteworthy that these blends show some positive deviation for the tensile strengths at yield and break from the ideal additive behavior which is usually predicted by the so-called mixing rule [22]. A parallel could be drawn between the higher mechanical performances of the SBR-2-containing blends and the higher interfacial strength of the PS/SBR-2/PE three-layer assembly compared to the SBR-1-based systems.…”
Section: Tensile Properties and Impact Strengthmentioning
confidence: 57%
“…Except for the elongation, the superiority of the SBR-2-containing blends is clear over the SBR-1 counterparts. It is noteworthy that these blends show some positive deviation for the tensile strengths at yield and break from the ideal additive behavior which is usually predicted by the so-called mixing rule [22]. A parallel could be drawn between the higher mechanical performances of the SBR-2-containing blends and the higher interfacial strength of the PS/SBR-2/PE three-layer assembly compared to the SBR-1-based systems.…”
Section: Tensile Properties and Impact Strengthmentioning
confidence: 57%
“…Figure 4 illustrates the yield stress-composition relationship for the PVDF/PA6 blends and a small negative deviation. Recent studies have suggested that the yield behaviour of polymer blends is affected by the interfacial adhesion [31,[33][34]37]. Pukanszky et al [31][32][33][34][35][36][37] have proposed the upper and lower values for the yield stress, in case of extreme values of interfacial adhesion.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Recent studies have suggested that the yield behaviour of polymer blends is affected by the interfacial adhesion [31,[33][34]37]. Pukanszky et al [31][32][33][34][35][36][37] have proposed the upper and lower values for the yield stress, in case of extreme values of interfacial adhesion. When the interfacial adhesion is strong enough for the stress transfer to occur between two phases, the yield stress would obey the law of mixtures (the upper value):…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…8 Good adhesion of PC and PMMA is exploited by use of a PMMA shell on core-shell impact modifiers for PC. Although both PMMA and SAN adhere well to PC, the effect of adhesion on yielding and deformation of PC/PMMA blends and PC/SAN blends has never been directly compared.…”
Section: Introductionmentioning
confidence: 99%